An exploratory study on IT governance implementations: towards strategic business/ IT alignment in the public sector of Malaysia / Wan Meliza Wan Ibrahim - Wan Ibrahim, Wan Meliza (2014)
The emerging use of Information Technology (IT) in this digital era is undeniable as it embarks the competitiveness and effectiveness of the business operations. IT has become an important enabler in doing business. IT is being used in almost all business functions. Information Technology governance (ITG) is the way how to put together the business processes using IT to achieve strategic business requirements. However, without good governance, strategic business and IT alignment could not be achieved. This study will explore on the implementation of ITG in Malaysian Public Sector and to identify the factors and challenges in day-to-day practice of ITG that will lead towards strategic business/IT alignment. Many literatures suggest that organization need to reach for strategic business/IT alignment to be able to compete with competitors and to do business transformation. To achieve this purpose, Qualitative research methodology will be used. Qualitative data were collected via interviews with current and future IT managers in the Public Sector of Malaysia. Expected results from this study would be the identified levels of implementation, factors and challenges that drive the strategic alignment of business and IT.